Theme-Based Learning in Teaching Speaking Skill (A Pre-experimental Study of Tenth-Graders in One of Senior High Schools in Garut) - Ira Destiani; Tatang Setia; Muhamad Taufik Hidayat (English Education and Applied Linguistics Journal (EEAL Journal), 2020)
This study was conducted to investigate the effectiveness of theme-based learning in teaching speaking skill. Specific objectives of this study were to find out: (1) whether theme-based learning is effective in improving students’ speaking skill and (2) students’ responses toward the implementation of this teaching method. This study, that was conducted in one of senior high schools in Garut to 37 students used quantitative method collaborated with pre-experimental design. The data in this study were collected by using speaking test; pre-test and post-test and interview. The speaking tests then analyzed and interpreted by using t-test to find out whether theme-based learning is effective in improving students’ speaking skill or not. Meanwhile, the interview then classified into description to find out students’ responses toward the implementation of theme-based learning. The result of this study showed that theme-based learning is effective in improving students’ speaking skill. The pre-test score indicated mean 9.216 and post-test score indicated mean 15.02 with t-test showed tobserve > tcritical (11.264 > 1.6893). In addition, the result of the interview that was conducted to the 10 students showed 100% positive responses